USING ENGLISH VIDEOS FROM INSTAGRAM TO INCREASE STUDENTS PRONUNCIATION SKILL AT THE EIGHTH GRADE OF SMPN 33 MAKASSAR - Syamsuriati; Baso, Farisha Andi; Ilmiah (Journal of Computer Interaction in Education, 2021)
This research was conducted to find out whether Instagram can increase the students’ Pronunciation skill. The research was obtained at the eighth-grade students of SMPN 33 Makassar. Using Quasi Experimental by taking 2 classes as samples and each class including 28 students. So, the total number of all samples are 56 students. This research found that Instagram videos can increase the students’ Pronunciation skill. The improvement can be seen by mean score of Pre-test in Experimental class was 44.64 and mean score of Post-test was 66.43. Meanwhile, mean score of Pre-test in Controlled class was 47.50 and mean score of Post-test was 42.50. This research Hypothesis concluded that Ha was accepted and Ho was refused showed by the T-test value was greater than the T-table (6.461>1.703), it means that using Instagram videos can increase the students’ English Pronunciation skill.